ANALISIS STRATEGI PENINGKATAN PENJUALAN PADA PERUSAHAAN TELUR AYAM RAS PT. HAVIN FARM DESA PETUNG, KECAMATAN PAKIS, KABUPATEN MAGELANG TAHUN 2023 - Bellinda Dwi Astuti (Journal Accounting International Mount Hope, 2024)
From this research found the background of the problem is the increasing competition of business resulting in the good and bad effects for each industry of this egg farming chicken, which in this endeavour is required to continue to analyze the environment both internally and externally exists in particular at the company farming PT Havin Farm. Besides there are problems in this research is what strategy has been done by the company to increase the sale of egg business chicken and can know any negative impact, strength, and threats as well as see opportunities to be able to increase attractiveness of the public to stay in buying eggs at the farm company. This study discusses the relationship between the marketing strategy that includes, the understanding of strategy, the definition of marketing, understanding of marketing strategy, eggs of breeds, and SWOT analysis. The results of this study show that PT Havin Farm can obtain a value or score IFAS 2.3 which means that the internal position in this company is strong enough, whereas at a level or score of EFAS 2.92 it shows that the company can respond to the opportunities already existing by avoiding the threats that exist in the breeding sector of eggs and breeds in P.T. Havin farm.